2012
DOI: 10.1371/journal.pone.0048839
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Survival in HIV Positive Patients with up to 15 Years of Antiretroviral Therapy

Abstract: BackgroundLife expectancy has increased for newly diagnosed HIV patients since the inception of combination antiretroviral treatment (cART), but there remains a need to better understand the characteristics of long-term survival in HIV-positive patients. We examined long-term survival in HIV-positive patients receiving cART in the Australian HIV Observational Database (AHOD), to describe changes in mortality compared to the general population and to develop longer-term survival models.MethodsData were examined… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
50
1
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 68 publications
(53 citation statements)
references
References 23 publications
1
50
1
1
Order By: Relevance
“…Accordingly, HIV/AIDS is now characterised as a chronic but manageable disease. 6,7 Use of HAART for treatment of HIV infection has made considerable changes in the natural progression of the disease. 8 The effectiveness of HAART varies between countries because drug metabolism is affected by various factors such as burden of background diseases (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, HIV/AIDS is now characterised as a chronic but manageable disease. 6,7 Use of HAART for treatment of HIV infection has made considerable changes in the natural progression of the disease. 8 The effectiveness of HAART varies between countries because drug metabolism is affected by various factors such as burden of background diseases (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…ART has been shown to be effective in reducing morbidity and mortality in patients infected with HIV [3, 4]. It averts 5.5 million deaths in low and middle income countries from the peak in 1995 until 2013.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have shown that ART prolongs and improves the quality of life of a person living with HIV. In some settings, survival of people living with HIV may be similar to that observed in HIV-negative populations [10][12]. Poor adherence to the appropriate ART dosing schedule selects for drug resistance and can shorten the regimens durability [13].…”
Section: Introductionmentioning
confidence: 99%